The mechanics of liquid foams: history and new developments - WEAIRE, DENIS; HUTZLER, STEFAN (My University, 2011)
The story of some recent developments in foam rheology is related at key points to the remarkable early contributions of Henry Princen, who pioneered the rigorous modern development of the subject. His general approach of introducing tractable geometrical models for foam structure and linking them to physicochemical properties at a smaller scale is still valid. It has however been amended to include the effects of disorder which are essential to the understanding of some properties, such as the variation of elastic modulus and yield stress with liquid fraction. Recent interest in foam rheology concerned the effect of shear localization in 2D foams, as was definitively demonstrated in 2001. This remains a challenge to theory, although continuum models have proved to be tractable and transparent, and have enjoyed some success.
PUBLISHED
Keywords: Condensed matter physics; Nanoscience & Materials